Self-Reported Medication Adherence in Patients With Ankylosing Spondylitis: The Role of Illness Perception and Medication Beliefs - Sena TOLU; Aylin REZVANİ and İlhan KARACAN and Derya BUGDAYCI and Habib Can KÜÇÜK and Ömer Faruk BUCAK and Teoman AYDIN (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate medication adherence in Turkish patients with ankylosing spondylitis (AS) and analyze the related factors for non-adherence. Patients and methods: Ninety-nine patients with AS (60 males, 39 females; mean age 41.3±8.4 years; range, 18 to 66 years) were included in the study. Sociodemographic and clinical data were collected. Disease activity (Bath Ankylosing Spondylitis Disease Activity Index, C-reactive protein, and erythrocyte sedimentation rate), functional status (Bath Ankylosing Spondylitis Functional Index), spinal pain and fatigue (visual analog scale), quality of life (Ankylosing Spondylitis Quality of Life), and depression and anxiety (Hospital Anxiety and Depression Scale) were evaluated. Adherence to anti-rheumatic drugs was elicited using the Compliance Questionnaire on Rheumatology (CQR). Medication beliefs were assessed using the Beliefs about Medicines Questionnaire (BMQ), and illness perception using the Brief Illness Perception Questionnaire (B-IPQ). Results: Non-adherence was reported in 64 patients (64.6%). No significant relationship between demographic, clinical, or psychological factors and adherence was found, except for disease duration (p=0.031). High B-IPQ treatment follow-up, illness coherence, and BMQ-Specific necessity scores were associated with good adherence (p=0.007, p=0.039, and p=0.002, respectively). BMQ-General overuse and harm scores showed an inverse correlation with the CQR score (p=0.005 r=-0.278; p=0.029 r=-0.219, respectively). Longer disease duration [odds ratio (OR): 0.98, 95% confidence interval (CI): 0.97-0.99] and higher B-IPQ item-1 score regarding the effect of the illness on the individual’s life (OR: 0.58, 95% CI: 0.42- 0.81) were important predictors of low adherence. Conclusion: Nearly three out of five AS patients were identified as at risk for non-adherence with the CQR. Medication adherence is influenced by the patient’s beliefs about medicines and illness perceptions, and these may be key targets for future interventions to improve medication adherence.